Situation Report: Romania, 11 October 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Prime Minister Manescu Visits Austria Foreign Minister Macovescu at Opening of UN General Assembly Todor Zhivkov Visits Romania Measures to Improve Scientific Research Ceausescu Inaugurates New Building at Stefan Gheorghiu Party Academy Ceausescu Discusses Warsaw Pact and Training with Army Party Aktif